Pelaksanaan Ekstrakurikuler Paduan Suara di SMP Angkasa Lanud Padang - Olong, Aholongan Nauli; Ardipal (Universitas Negeri Padang, 2023)
The purpose of this study is to describe the Extracurricular Implementation of Choir at SMP Angkasa Lanud Padang. This kind of study employs qualitative descriptive research techniques. The object of research is the implementation of choir extracurricular activities at SMP Angkasa Lanud Padang. This research instrument is the researcher himself who is assisted by supporting instruments such as documentation results. Data collection techniques are carried out by observation, interviews, documentation, and literature studies. Data analysis techniques by means of data collection, clarifying data, analyzing data, and inferring data. The results showed that the choir extracurricular program at SMP Angkasa Lanud Padang could run well following the correct steps and stages, starting with gathering students interested in participating in choir extracurricular activities, making training schedules and agendas, and providing materials. In the Extracurricular Choir Implementation, students can sing Bareh Solok songs together in a choir with two voices: soprano and alto. Choir extracurricular activities at SMP Angkasa Lanud Padang The results are quite good because they are supported by sufficient facilities. As well as teachers have successfully organized choir extracurricular activities.